Pengaruh Kemudahan, Risiko, Gaya Hidup, dan Kepercayaan Terhadap Perilaku Konsumtif Pengguna Shopee Paylater di Indonesia - Anggraeni, Ni Putu Novi; Darma, Gede Sri (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2023)
The purpose of this study is to investigate the impact of Shopee Paylater's user-friendliness, risk perception, lifestyle choices, and trust on Indonesian millennials and Generation Z consumers' buying habits. The study involves 250 participants chosen through purposive sampling and gathers data through online questionnaire surveys conducted via Google Forms. Quantitative analysis in this research is conducted using the Smart PLS 4.0 software platform. The findings of the research reveal that ease of use, risk perception, and lifestyle choices positively and significantly influence trust. Additionally, Certainly, a strong and meaningful link exists between lifestyle decisions and their impact on influencing spending habits. It's worth emphasizing that the direct impacts of user-friendliness and perceived risk on spending behavior are relatively limited. Importantly, the primary driver of spending behavior is lifestyle choices, while the influence of ease of use and risk factors is channeled indirectly through trust.